Getting To Know Phoneme And Its Benefits In Sound Science - Alvindi Alvindi; Nisa Febriyanti Tanjung; Thareq Ahmad Alqawwiy; Yani Lubis (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to find out how loanwords from other languages in Indonesian change their phonemes. Changes in vowel and consonant phonemes indicate these changes. The research method combines literature review techniques and qualitative descriptive methods. The data collected are taken from various literature sources and then grouped according to certain criteria. The results showed that language sounds are based on two premises: they usually form symmetrical patterns and the sounds of language usually interact with each other. Phonology also has hypotheses, which serve as the basis of its analysis in the following way, in addition to these two premises. When phonetically similar sounds contrast in minimal pairs, it is first necessary to treat them as different phonemes.